Genius of American politics - "Boorstin, Daniel J." (Chicago, 1953)
This volume is a revision of public lectures delivered at the University of Chicago in February and March 1952, under the Charles R. Walgreen Foundation for the Study of American Institutions. Professor Jerome G. Kerwin, director of the Foundation, has been especially helpful with his encouragement and criticism. Some of the materials of the lectures were developed in connection with my teaching at the University of Rome under a Fulbright appointment in 1950-51. Parts of chapter iii appeared in the William and Mary Quarterly for October, 1950. A grant from the Social Science Research Committee of the University of Chicago has aided the preparation of the manuscript. I particularly wish to thank William T. Bluhm, now of the department of political science of the University of Rochester, for his trenchant editorial advice.
Keywords: Political Science